Nanofibers in Ocular Drug Targeting and Tissue Engineering: Their Importance, Advantages, Advances, and Future Perspectives - Egemen Uzel; Meltem Ezgi Durgun; İmren Esentürk-Güzel; Sevgi Güngör; Yıldız Özsoy (MDPI AG, 2023)
Nanofibers are frequently encountered in daily life as a modern material with a wide range of applications. The important advantages of production techniques, such as being easy, cost effective, and industrially applicable are important factors in the preference for nanofibers. Nanofibers, which have a broad scope of use in the field of health, are preferred both in drug delivery systems and tissue engineering. Due to the biocompatible materials used in their construction, they are also frequently preferred in ocular applications. The fact that they have a long drug release time as a drug delivery system and have been used in corneal tissue studies, which have been successfully developed in tissue engineering, stand out as important advantages of nanofibers. This review examines nanofibers, their production techniques and general information, nanofiber-based ocular drug delivery systems, and tissue engineering concepts in detail.